Metformin in COVID-19: a magical role beyond the hyperglycemia - Gaurav Kumar Chaubey; Rahul Dilawari; Radheshyam Modanwal; Sharmila Talukdar; Asmita Dhiman; Manoj Raje (Exploration of Drug Science)
Coronavirus disease-2019 (COVID-19) has emerged as an aggressive viral infection in the last few years. Initially reported in the Wuhan area of the People’s Republic of China, it soon emerged across the globe. Researchers confront a worrying situation to rapidly develop effective strategies to combat this novel infection and its long-term aftereffects. To date, there have been myriad reports ranging from the repurposing of the classical antimalarial drug hydroxychloroquine to several other antiviral and anti-bacterial agents like remdesivir, favipiravir, and most recently azithromycin, which has entered clinical use in many countries for combating COVID-19 infections. Several studies have highlighted the nexus between COVID-19-associated morbidity and diabetes in a wide-ranging class of subjects ranging from pediatric cases to adults and patients with other co-morbidities. Metformin is a mainstay in the treatment of type 2 diabetes (T2D). It is safe, inexpensive, and effective and does more than merely control blood sugar levels. Important metabolites that encourage blood clotting and inflammation are also suppressed by metformin. Pro-inflammatory molecules are linked to obesity and T2D. Both are major risk factors for aggravated COVID-19. These characteristics gave rise to a hypothesis that metformin may find use as an efficacious treatment for COVID-19 especially if it decreases the inflammatory molecules that fuel the COVID-19 virus-induced effects. In this review, we attempt to elucidate the role of classical anti-diabetic medicine metformin in the treatment of COVID-19 infections by highlighting the pharmacological role of this drug during elevated glucose levels and insulin resistance. We examine how COVID-19 has correlations to diabetic physiology and thereby the possibility of repurposing metformin for COVID-19 treatment.